A Comparative Analysis of Fertility and Maternal and Child Mortality Indicators Before and During the COVID-19 Pandemic in Mazandaran Province - Marzieh Zamaniyan; Maboubeh Omid; Malihe Ghasemi Tirtashi; Ghasem Oveis; Fatemeh Jaefari; Seyed Mohsen Soleimani rad; Jamshid Yazdani charati; Mahmood Moosazadeh (Journal of Mazandaran University of Medical Sciences)
Background and purpose: Reproductive health is considered one of the most essential components for achieving sustainable development in various societies. The sudden emergence of the COVID-19 pandemic severely impacted reproductive and sexual health worldwide. Due to prolonged lockdowns, individuals faced financial hardships, leading to increased levels of stress, anxiety, and depression. These factors significantly influenced individuals' sexual behaviors. In this study, we examined and compared fertility indicators, as well as child and maternal mortality rates, before and after the COVID-19 pandemic. Materials and methods: This study was a descriptive-analytical, cross-sectional investigation. The statistical population included all women who visited healthcare centers from March 2011 to February 2022. Data related to the pre-COVID-19 period were obtained from the Deputy for Treatment, while fertility indicators were extracted from the Deputy for Health. Statistical analysis was performed using STATA version 14. Results: The maternal mortality rate due to pregnancy and childbirth complications more than doubled compared to previous years. The risk of stillbirth was 1.39 times higher than in the pre-pandemic period. However, no significant differences were observed in neonatal and child mortality rates across different age groups between the pre-pandemic and pandemic periods. Conclusion: Based on the results of this study, which demonstrate the direct impact of the COVID-19 pandemic on maternal and fetal mortality rates, as well as fertility rates, it is essential for policymakers to adopt new strategies to address such epidemics and crises. Clear and consistent guidelines for the provision of high-quality sexual and reproductive health services are urgently requir